Selective fertility - the examples of perinatal death and preeclampsia - Rolf Skjærven; Kari Klungsøyr Melve (Norsk Forening for Epidemiologi, 2007)
Introduction. Studies of foetal or perinatal losses are hampered by the fact that a woman's pregnancies are not independent events, making traditional "cross sectional" design and analyses difficult. A complicating issue is the mechanism of "selective fertility". Selective fertility is the tendency for a woman to replace aperinatal loss with a new pregnancy until the desired number of children is attained. We wanted to evaluate the effects of selective fertility related to perinatal deaths and to preeclamptic pregnancies, using data covering four decades. Material and Methods. We use data from the Medical Birth Registry of Norway, covering the years 1967-2006, altogether 2.3 million births, organized into 1.1 million sibships with the mother as the unit of analysis. Results. Following a perinatal death, the continuation to a next pregnancy is higher then after a live birth, and this elevation of 'fertility' has increased over time. After two perinatal losses, the continuation is more then doubled. On the other hand, continuing to a next pregnancy is reduced after a preeclamptic pregnancy, and after two preeclamptic pregnancies the reduction corresponds to 25%. Conclusions. These two examples show that samples of births are strongly hampered by self-selection to pregnancy. Therefore, data organized into sibships should be obligatory for studies in perinatal epidemiology. Perinatal epidemiology is in need for analytical designs that account for dependencies in data.